INTEGRASI LITERASI DIGITAL, DOMPET DIGITAL DAN BAHASA INGGRIS DALAM MENINGKATKAN EFEKTIVITAS PEMASARAN UMKM - Sirait, Fransiska; Batubara, Lika Silvia (POLITEKNIK LP3I JAKARTA, 2026)
The purpose of this study is to analyze the effect of the integration of digital literacy, the use of digital wallets, and English language proficiency on the marketing effectiveness of Micro, Small, and Medium Enterprises (MSMEs). The focus of the research is directed toward examining how these three factors interact in enhancing market reach, promotional efficiency, and the competitiveness of MSMEs in the digital era. Based on the survey results, it was found that the digital marketing strategies implemented have not yet produced optimal outcomes. The promotional activities remain passive, unstructured, and have not had a significant impact on increasing sales. This low level of marketing effectiveness is attributed to the absence of consistent promotional strategies, limited understanding of branding concepts, and the underutilization of analytical features and customer review tools. Therefore, the researchers developed training programs delivered through a website and disseminated them to participating MSMEs. The research findings indicate that all three types of website-based training—digital literacy, the use of digital wallets, and English language skills—have a positive effect on improving the marketing effectiveness of MSMEs. Digital literacy enhances promotional capabilities, digital wallets facilitate transaction convenience, and English language skills expand market reach. The integration of these three components through website-based training serves as an effective strategy for improving the competitiveness and marketing performance of MSMEs in the digital economy era.